Citizen Perception and Ex Ante Acceptance of a Low-Emission Zone Implementation in a Medium-Sized Spanish City - Montaña Jiménez-Espada; Francisco Manuel Martínez García; Rafael González-Escobar (Buildings, 2023)
The public decision-making process at the municipal level becomes extremely complicated for government managers when unpopular measures must be adopted. In this sense, citizen participation processes become a tool of undoubted added value that allows municipalities to adapt their policies to the needs and feelings of their inhabitants. The aim of this research was to focus on addressing the point of view of the citizens of a medium-sized Spanish city in the face of the imminent implementation of a low-emission zone, in order to identify which aspects were of concern to citizens. The methodology used in the research was based on a declared preferences survey that allowed us to determine the daily behaviour of the user in terms of urban mobility and to anticipate the citizen’s reaction to the implementation of socially unacceptable initiatives, such as restrictions on access, circulation, and the parking of vehicles. The results obtained in relation to the consultation on alternative measures to tackle pollution, noise and traffic jams showed that citizens are receptive to improvements in universal accessibility, subsidies for public transport, increased road safety for PMV’s infrastructure, subsidies for the purchase of environmentally friendly vehicles and PMV, and the promotion of pedestrianisation. However, there are undoubted threats to the implementation of the LEZ, such as the lack of acceptance of the measure. Therefore, it is considered imperative for public administrations to work on the search for sustainable actions that contribute to improving the degree of compliance with the measure, while at the same time making an effort to disseminate the advantages of the LEZ for the quality of life and health of citizens (through information campaigns). There is a knowledge gap in scientific research on the ex ante assessment of the effects of possible transport measures to improve air quality in city centres and consultation through citizen participation. It is estimated that the resolution of this research gap could contribute to a more feasible, reasonable, and effective implementation of various urban mobility policies in medium-sized Spanish cities.